Alcohol and substance abuse, depression and suicide attempts after Roux-en-Y gastric bypass surgery. Issue 10 (28th July 2016) - Backman, O; Stockeld, D; Rasmussen, F; Näslund, E; Marsk, R
Abstract: Background: Small studies suggest that subjects who have undergone bariatric surgery are at increased risk of suicide, alcohol and substance use disorders. This population-based cohort study aimed to assess the incidence of treatment for alcohol and substance use disorders, depression and attempted suicide after primary Roux-en-Y gastric bypass (RYGB). Methods: All patients who underwent primary RYGB in Sweden between 2001 and 2010 were included. Incidence of hospital admission for alcohol and substance use disorders, depression and suicide attempt was measured, along with the number of drugs prescribed. This cohort was compared with a large age-matched, non-obese reference cohort based on the Swedish population. Inpatient care and prescribed drugs registers were used. Results: Before RYGB surgery, women, but not men, were at higher risk of being diagnosed with alcohol and substance use disorder compared with the reference cohort. After surgery, this was the case for both sexes. The risk of being diagnosed and treated for depression remained raised after surgery. Suicide attempts were significantly increased after RYGB. The adjusted hazard ratio for attempted suicide in the RYGB cohort after surgery compared with the general non-obese population was 2·85 (95 per cent c.i. 2·40 to 3·39). Conclusion: Patients who have undergone RYGB are at an increased risk of being diagnosed with alcohol and substance use, with an increased rate of attempted suicide compared with a non-obese general population cohort. Abstract : Does not fix mental health problems